PENGARUH PENYULUHAN TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG TANDA â TANDA PUBERTAS DI KELAS VII SMP AL-MALIKI DESA LEDOK WETAN KECAMATAN BOJONEGORO KABUPATEN BOJONEGORO TAHUN 2014 - PATONAH, SITI; W, ATIK SETIAWAN; Setiyani, Melinda Eriqga (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2016)
ABSTRACTPuberty is a period of transition from childhood into adolescence or adulthood. Today many teenagers found that lack of knowledge about the signs of puberty in girls because of less active in seeking information through print media and technology. The purpose of this study was to analyze the effect of education on knowledge of young women about the signs of puberty in junior high Maliki Wetan Ledok Village District of Bojonegoro Bojonegoro 2014..The method used is analytic. The approach used in this study is experimental. The total sample was 47 respondents. In this study sampling means that the sample probability sampling technique with a total sampling technique. Later in doing the editing, coding, scoring and then compared with a table of comparison (comparison).The results of this study obtained showed that young women with good knowledge before counseling as much as 3 respondents (6.4%), whereas a good knowledge after counseling increased to 38 respondents (80.9%).Â Most of the girls had a good knowledge performed after counseling. For an effort to increase the knowledge of young women in need of cooperation with the UKs officers to conduct outreach on an ongoing basis, but it is expected that the young women to be able to acquire knowledge by utilizing mass media and modern technology to acquire knowledge in order to be always keeping in respondents knowledge, apply and can have a readiness in the face of puberty.Â Â Keywords: Puberty, Science, Counseling, Teen